STRATEGI PENGENDALIAN MUTASI SANTRI DI PESANTREN DARUSSALAM BLOKAGUNG - Anisa Nabella; Nadir, Mirhabun; Aimah, Siti (IAI Darussalam, 2023)
The purpose of this study was to describe and analyze the planning, implementation, and evaluation of the strategy for controlling student mutations at the Darussalam Blokagung Islamic Boarding School, Banyuwangi. The research method uses descriptive qualitative, data collection through interviews, observation and documentation. Data analysis techniques use data reduction, data presentation and drawing conclusions. Checking the validity of the data using triargulation of sources, methods and observers. The results showed that: (1) planning a strategy for controlling student mutations, namely formulating standard student mutations based on vision and mission, analyzing data on student mutations, forming a Department for controlling student mutations, conducting outreach to students and guardians of students (2) Implementation of strategies for controlling student mutations, namely the obligation of the santri to fulfill the procedure for transferring students which involves the caretakers of the Darussalam Islamic Boarding School, cooperation between the students, the guardians of the students, the pesantren administrators and the Department for transferring students. (3) Evaluation of the strategy for controlling student mutations, where there is supervision between caregivers and pesantren administrators, improving the quality of students' abilities and evaluating the results of students' abilities, forming accountability reports on student mutation control data at the Darussalam Blokagung Islamic Boarding School.